Integrative analysis of taurine metabolism-related genes prognostic signature with immunotherapy and identification of ABCB1 and GORASP1 as key genes in nasopharyngeal carcinoma - Zhang Feng; Yuhang Yang; Wenqi Luo; Jinqing Li; Zhenlian Xie; Long Zuo; Meijiao Duan; Dongzhi Zuo; Ruwei MO; Xuejing Tang; Shijiang Yi; Xiaosong He; et al. (Amino Acids)
Abstract Taurine is an amino acid with several physiological functions and has been shown to be involved in the anti-tumor of human nasopharyngeal carcinoma (NPC) cells. However, the role of taurine metabolism-related genes (TMRGs) in NPC has not been reported. We integrated data from the Genecards, Kyoto Encyclopedia of Genes and Genomes (KEGG), and Gene Expression Omnibus(GEO) databases to identify differentially expressed genes associated with taurine metabolism in NPC patients. Gene Ontology (GO) and KEGG analyses were conducted to investigate the underlying mechanisms. Subsequently, Cox regression and Least Absolute Shrinkage and Selection Operator (LASSO) regression analyses were performed to construct a taurine metabolism-related prognostic signature. Survival, medication sensitivity, and immunological microenvironment evaluations were performed to assess the prognostic utility of the model. Finally, immunohistochemistry (IHC) experiments were performed to validate the model’s prognostic reliability. In addition, we further verified the reliability of our research results through molecular docking and single-cell sequencing. Our prognostic model was based on three pivotal TMRGs (ABCB1, GORASP1, and EZH2). Functional analysis revealed a strong association between TMRGs and miRNAs in cancer. Notably, increased risk scores correlated with worsening tumor malignancy and prognosis. Significant disparities in immune microenvironment, immune checkpoints, and drug sensitivity were observed between the high- and low-risk groups. The protein expression patterns of the selected genes in clinical NPC samples were validated using immunohistochemistry. Molecular docking verified the interaction between these three core genes and taurine, which was further supported by single-cell sequencing showing significant expression variation among different cell clusters in NPC. We had elucidated the functions, therapeutic potential, and prognostic significance of three key genes related to taurine metabolism in NPC through multidimensional research and experimental validation. This research provided valuable insights and potential avenues for improved NPC management.